PTSD Biomarker Database: deep dive metadatabase for PTSD biomarkers, visualizations and analysis tools. (29th June 2019) - Domingo-Fernández, Daniel; Provost, Allison; Kodamullil, Alpha Tom; Marín-Llaó, Josep; Lasseter, Heather; Diaz, Kristophe; Daskalakis, Nikolaos P; Lancashire, Lee; Hofmann-Apitius, Martin; Haas, Magali
Abstract: The PTSD Biomarker Database (PTSDDB) is a database that provides a landscape view of physiological markers being studied as putative biomarkers in the current post-traumatic stress disorder (PTSD) literature to enable researchers to explore and compare findings quickly. The PTSDDB currently contains over 900 biomarkers and their relevant information from 109 original articles published from 1997 to 2017. Further, the curated content stored in this database is complemented by a web application consisting of multiple interactive visualizations that enable the investigation of biomarker knowledge in PTSD (e.g. clinical study metadata, biomarker findings, experimental methods, etc.) by compiling results from biomarker studies to visualize the level of evidence for single biomarkers and across functional categories. This resource is the first attempt, to the best of our knowledge, to capture and organize biomarker and metadata in the area of PTSD for storage in a comprehensive database that may, in turn, facilitate future analysis and research in the field.